MicroRNA-21 plays a role in exacerbating chronic obstructive pulmonary disease by regulating necroptosis and apoptosis in bronchial epithelial cells - Zhengpeng Zeng; Xuelian Liu; Fei Xiang; Xue He; Jiahui Li; Hanying Liu; Lihua Xie (Tobacco Induced Diseases)
Introduction Bronchial epithelial cell damage is an important determinant of the severity of chronic obstructive pulmonary (COPD). However, the exact molecular mechanisms underlying this cell death in COPD development are not well understood. This study investigates the involvement of microRNA-21 (miR-21/ miRNA-21) in COPD and its underlying molecular mechanism.